2017
DOI: 10.1007/978-3-319-59448-4_45
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Haemodynamic Remodeling in Fetal Aortic Coarctation Using a Lumped Model of the Circulation

Abstract: Abstract. Introduction: Aortic coarctation is one of the most difficult cardiac defects to diagnose before birth, and it accounts for 8% of congenital heart diseases. Antenatal diagnosis is crucial for early treatment of the neonate and to decrease the risk of morbidity and mortality; however the fetal hemodynamic changes are not fully understood and current imaging methods are limited to accurately diagnosis this congenital defect. Objective: We propose to use a lumped model of the fetal circulation to provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…This is in agreement with other studies that reported that bidirectional isthmic flow or isthmic flow reversal has a low sensitivity and specificity in detecting CoA prenatally (13,(34)(35)(36). Furthermore, not only the degree but also the site of the isthmic narrowing may play a role in the occurrence of fetal systolic isthmic flow reversal (37). Furthermore, the definitive narrowing in the aortic isthmus may only occur in the neonatal period when the arterial duct closes (22).…”
Section: Discrimination Between True Coa and False Positives With Hel...supporting
confidence: 92%
“…This is in agreement with other studies that reported that bidirectional isthmic flow or isthmic flow reversal has a low sensitivity and specificity in detecting CoA prenatally (13,(34)(35)(36). Furthermore, not only the degree but also the site of the isthmic narrowing may play a role in the occurrence of fetal systolic isthmic flow reversal (37). Furthermore, the definitive narrowing in the aortic isthmus may only occur in the neonatal period when the arterial duct closes (22).…”
Section: Discrimination Between True Coa and False Positives With Hel...supporting
confidence: 92%